Aplospojaveedins A–C, unusual sulfur-containing alkaloids produced by the endophytic fungus Aplosporella javeedii using OSMAC strategy - Gao, Ying; Frank, Marian; Teusch, Nicole; Woschko, Dennis; Janiak, Christoph; Mándi, Attila; Kurtán, Tibor; Hartmann, Rudolf; Schiedlauske, Katja; van Geelen, Lasse; Kalscheuer, Rainer; Kaiser, Jesko; et al. (Frontiers in Microbiology, 2024)
Three sulfur-containing alkaloids aplospojaveedins A-C (1-3) with a hitherto undescribed carbon skeleton comprising octahy-dronaphthalene, α, β-unsaturated lactam and glycine-cysteine moieties were isolated from Aplosporella javeedii. Their structures were elucidated by 1D and 2D NMR spectroscopy, HR-MS, X-ray diffraction analysis, DFT-NMR and TDDFT-ECD calculations. A plausible biosynthetic pathway and putative targets are described. The blind docking suggested that 1 -3 may have functional effects on several putative targets such as the GPCR cannabinoid receptor 2 or the integrin α5β1 complex.